A Closer Look at "Taller-Than-Wide" Thyroid Nodules: Examining Dimension Ratio to Predict Malignancy. (August 2022) - Mattingly, Aviva S.; Noel, Julia E.; Orloff, Lisa A.
Objective: To evaluate nodule height-to-width ratio as a continuous variable predicting likelihood of thyroid malignancy. Study Design: Retrospective cohort study. Setting: All study information was collected from a single academic tertiary care hospital. Methods: Subjects included adult patients with thyroid nodules who underwent thyroid surgery between 2010 and 2020. The following variables were collected: patient demographics, nodule dimensions via ultrasound, fine-needle aspiration biopsy results, and surgical pathology results. Statistical analysis included logistic regression modeling malignancy with variables of interest. We used a receiver operating characteristic curve to assess the discriminatory value of variables. Results: Height-to-width ratio, as a continuous variable, was associated with malignancy (with each 0.1 increase in ratio; odds ratio [OR], 1.25; 95% CI, 1.14-1.37). The same relationship was true for height-to-length ratio (OR, 1.36; 95% CI, 1.24-1.56). The area under the receiver operating characteristic curve for height-to-width ratio was 63.7%. In line with current emphasis on the transverse ultrasound view, we determined 4 different height-to-width ratio intervals: <0.8, 0.8 to <1.0, 1.0 to <1.5, and ≥1.5. Likelihood ratios of malignancy for each interval were 0.6, 1.0, 2.3, and 4.9, respectively. Conclusion: Our results support the association between greater height-to-width ratio and malignancy but suggest that a multilevel rather than binary variable improves prediction. The likelihood ratios at different intervals give a more nuanced view of how height-to-width ratio predicts malignancy. With continuing review of guidelines for thyroid nodule biopsy, it is important to consider these data for any point total attributed to shape.